Subfertility: philosophy and methodology of the problem. Part II - И. З. Гладчук; В. В. Дощечкин (Publishing House TRILIST, 2018)
The review-philosophical work is devoted to the problem of subfertility. The low fecundity of a part of individuals who are within the fertile population is one of the most urgent social and medical problems of modern society. Usually there are no obvious reasons for fertility decline in subfertile people. The work considers a paradigm in which the low existing fertility in a part of the population is able to find an explanation in connection with the existence of various normal variants of the development of organs and tissues of the reproductive system. Normally the time to pregnancy in subfertile individuals is increased. Timing in general is a major factor in optimizing the management of a couple with unexplained infertility which should be taken into account in the management of infertility. The work presents modern terminology used in reproductive medicine. The paper shows the methodological problems that can arise in the assessment of individual fertility potential. A "fertility scale" is presented that can help in assessing fertility and determining the algorithm for management of infertile couple. The modern understanding of the etiology of subfertility/infertility is showed. The role of evidential and causal decision theory used for understanding of the pathogenesis of fertility decline is discussed. Also the philosophical view on the problem of unexplained infertility and outlines approaches to its solution, which are based on the diagnosis of anatomical and physiological (physical) features of the reproductive system of subfertile individuals are presented. Part II of the article considers the cause-effect relationships characteristic of subfertility and infertility, as well as methods that allow better understanding of such connections. The problem of heterogeneity of compared statistical series, the role of external and internal factors in the development of subfertility and infertility, a number of factors affecting fertility decline, the obligatory conditions for conception and the place of violations of these conditions in the structure of infertility causes, the role of "obvious" and "non-obvious" fertility will discussed. Main principles for optimization of conception conditions and the modern approaches to the management of couples with unexplained infertility are set out in the continuation of the article. The special role of transvaginal sonography in the study of the nature of subfertility and the diagnosis of the reproductive system development features is shown.